ANALISIS PENGARUH PRODUK, PERSONIL, DAN PROMOSI TERHADAP KEPUASAN PELANGGAN PADA PT. MNET INDONESIA - Fitry Yani Herlina; Rusda Irawati (Politeknik Negeri Batam, 2017)
This research is motivated by the needs of society and the conditions of service business competition intensifies, so the company must create a new marketing strategy to maintain and gain market share higher. As for the issue of this research is